An ideal kitchen - Graham, Cecile Agnes (My University, 1908)
Introduction: When we speak of the kitchen we mean the woman’s workshop. Perhaps no kind of work is more want to be irksome than that of housekeeping, and one reason for this is that it is done so poorly. The atmosphere of contentment is wanting. To remedy this, the kitchen of this home should be thoughtfully planned and well equipped with the best known appliances.
Citation: Graham, Cecile Agnes. An ideal kitchen. Senior thesis, Kansas State Agricultural College, 1908.
Keywords: Domestic Science; Home Economics; Kitchens; Graduating theses; Senior theses; Theses